BIARLAH kupu-kupu mengajariku : antologi cerpen SMP N 1 Karangmojo Gunung Kidul Yogyakarta/Sc Penulis Kelas ekstrakurikuler SMP N 1 Karangmojo Gunung Kidul Yogyakarta...Ed.1 (Bimotry, 2009)
ix, 140 hlm.: ilus.; 21 cm